Mapping ESG disclosure (2004-2025): a bibliometric review and evidence-based core metric set - Uswatun Hasanah; Oki Prayogi; Ayunda Fatmasari; Oppie Meisya Tanjung; Hajatina Hajatina (Insight Management Journal, 2026)
This study maps the intellectual landscape of ESG disclosure research and proposes a concise set of auditable and comparable ESG indicators. Using a Scopus corpus covering 2004–2025 (n = 681), the study applies bibliometric analysis with VOSviewer and Biblioshiny through co-occurrence, co-citation, and citation network analysis. The findings show sustained publication growth, increasing international collaboration, and thematic concentrations around financial performance, corporate governance, CSR, and sustainability reporting. Citation structures further reveal strong linkages between governance mechanisms, disclosure quality, and firm value. Based on these network patterns, the study develops a core metric set using four selection criteria: financial materiality, auditability, comparability through alignment with ISSB, GRI, and ESRS, and proportionality for SMEs. The proposed indicators include GHG emissions intensity, energy intensity, total recordable injury rate (TRIR), employee turnover, board independence, audit committee activity, ESG risk-management policy, and machine-readable reporting formats. This study contributes by consolidating twenty-one years of ESG disclosure scholarship and translating bibliometric evidence into a practical starting point for standardized, decision-useful, and assurance-ready reporting. However, the study is limited to Scopus-indexed publications and does not empirically test the proposed indicators in organizational practice. Future research should expand the database, include non-English and regional publications, and validate the proposed indicators across sectors, jurisdictions, and firm sizes, particularly in SMEs and developing economies.